Association Between Emotional Regulation and Internet Addiction in Nursing Students - Ayu Julea Ketty; Jenny Deventi Kore Djami; Merci Theresiani Febrianti Tonael; Maria Veronika Ayu Florensa; Novita Susilawati Barus (GLOBAL HEALTH SCIENCE GROUP, 2024)
The use of the internet in higher education is very helpful for the learning process, including for nursing students. The use of the internet has increased since the Covid-19 pandemic provides both benefits and risks for students. Excessive internet use can have an impact on an individual's emotions. Objectives: This study aimed to identify the association between emotional regulation and internet addiction in nursing students. Method: the quantitative correlational design was used in this study. About 279 nursing students were obtained using the purposive sampling technique. Emotion Regulation Questionnaire (cronbach α for the suppression category 0.707 and 0.761 the reappraisal category) and Internet Addiction Test questionnaire (cronbach α 0.895)was used in study. The data were analyzed by univariate and Spearman rank-order bivariate analysis. Results: The nursing students tended to use cognitive appraisal (95.3%) and expressive suppression (87.1%) as a strategy of emotional regulation. The level of internet addiction of the students was mild (40.1%), moderate (29%) and severe (2.5%). There is no relationship between emotion regulation and internet addiction of nursing students (cognitive appraisal p=0.882; expressive suppression p=0.617). Even though the students were in mild internet addiction, they could regulate their emotion well. Conclusions Emotion regulation is not the only thing that can cause internet addiction. The ability to early recognize the symptoms of internet addiction is needed to prevent the condition becoming severe.